A HISTORICAL PERSPECTIVE AND CHALLENGES FOR SECRETARIAL PROFESSION - Mambo, Lenda (JIU (Jurnal Ilmiah Unklab); Volume 18 No.2, 2014 JIU UNKLAB, 2014)
Secretary is centuries-old profession which had contributed to the development of human civilization since the ancient time.  It performs both clerical and administrative functions in the government, church, and business as well.  As a profession, it has evolved as the business and work environment change.  Today the title administrative professional has redefined the roles and responsibilities of the office secretary to a wider and broader management function as partners of the executives and the CEOs, not merely as subordinates that follow instruction but as partners to assist them in the process of decision making.